Blood naltrexone levels over time following naltrexone implant - Ngo, H.; Arnold-Reed, D.; Hansson, R.; Tait, Robert; Hulse, G. (2008)
Aims: Oral naltrexone is used in the management of both heroin and alcohol dependence. However, poor compliance has limited its clinical utility. The study's objective was to determine the period of therapeutic coverage (= 2 ng/ml) provided by a 3.3 g naltrexone subcutaneous implant compared with existing data on 1.1 g and 2.2 g implants. Methods: We assessed free blood naltrexone levels following treatment with a 3.3 g naltrexone implant in heroin dependent patients (n = 50) in Perth, Western Australia. Results were compared with previously collated data for patients treated with either a 1.1 g (n = 10) or 2.2 g (n = 24) implant. Results: Following 3.3 g naltrexone implant treatment, free blood naltrexone levels remained above 2 ng/ml for 145 days (95% CI 125-167). In comparison, 1.1 g or 2.2 g implant treatment resulted in 95 days (95% CI 69-121) and 136 days (95% CI 114-158) coverage, respectively. Conclusions: The 3.3 g implant provides longer therapeutic coverage than the 1.1 g implant but not significantly longer than the 2.2 g implant. © 2007 Elsevier Inc. All rights reserved.